Poverty traps, economic inequality and delinquent incentives (2013)
This paper explores theoretical linkages between poverty traps, economic inequalityand delinquency in a perfect competition overlapping generations model characterizedby dual legal production sectors and one illegal sector. The model positsan absence of credit for human capital accumulation, which generates barriers toskilled educational attainment. We find that the existence of a poverty trap underconditions of sufficient initial economic inequality and costly indivisible humancapital investment generates persistent delinquency in the long run. We examinesteady state changes caused by shocks that increase skilled wages or reduceland assets available to the unskilled, finding that these shocks produce outbursts of delinquency that die out later if the shocks are temporary but increases permanentlyotherwise. We also find that an increase on relative poverty has anambiguous effect on long run delinquency rates while an increased focus on lawenforcement policies, intended to increase deterrence and incapacitation, reducesdelinquency in the long run and increases wealth inequality.